Intensification of the Atlantic Water Supply to the Arctic Ocean Through Fram Strait Induced by Arctic Sea Ice Decline. Issue 3 (3rd February 2020) - Wang, Qiang; Wekerle, Claudia; Wang, Xuezhu; Danilov, Sergey; Koldunov, Nikolay; Sein, Dmitry; Sidorenko, Dmitry; von Appen, Wilken‐Jon; Jung, Thomas
Abstract: Substantial changes have occurred in the Arctic Ocean in the last decades. Not only sea ice has retreated significantly, but also the ocean at middepth showed a warming tendency. By using simulations we identified a mechanism that intensifies the upward trend in ocean heat supply to the Arctic Ocean through Fram Strait. The reduction in sea ice export through Fram Strait induced by Arctic sea ice decline increases the salinity in the Greenland Sea, which lowers the sea surface height and strengthens the cyclonic gyre circulation in the Nordic Seas. The Atlantic Water volume transport to the Nordic Seas and Arctic Ocean is consequently strengthened. This enhances the warming trend of the Arctic Atlantic Water layer, potentially contributing to the Arctic "Atlantification." Our study suggests that the Nordic Seas can play the role of a switchyard to influence the heat budget of the Arctic Ocean. Plain Language Summary: The Arctic sea ice decline is among the key indications of climate change, which has strong impacts on the environment, human beings, and biodiversity. In this paper we found that the Arctic sea ice decline at the surface can even cause Arctic Ocean warming at middepth by intensifying the upward trend of ocean heat supply to the Arctic Ocean through Fram Strait. The Nordic Seas play the role of a switchyard for the involved processes: The sea ice decline reduces the sea ice export through Fram Strait, which further increases the salinity in the Greenland Sea. Consequently, in the Nordic Seas the sea surface height decreases and the gyre circulation strengthens. These changes then increase the Atlantic Water inflow to the Nordic Seas and the Arctic Ocean, causing significant warming in the Atlantic Water layer of the Arctic Ocean. The changes in the ocean heat budget have strong implications on potential feedbacks to sea ice decline through basal melting in a future warming climate. The intensification of the Atlantic Water volume transport through Fram Strait can impact not only the Arctic heat budget but also potentially the nutrient budget and the primary production. Key Points: The decline of Arctic sea ice reduces its export, thus increasing the salinity in Greenland Sea This reduces the sea surface height and speeds up the gyre circulation in Greenland and Nordic Seas The consequently enhanced Atlantic Water transport intensifies the warming at Fram Strait and in the Arctic Ocean